2004
DOI: 10.1509/jmkr.41.2.197.28667
|View full text |Cite
|
Sign up to set email alerts
|

When Corporate Image Affects Product Evaluations: The Moderating Role of Perceived Risk

Abstract: In two experiments, the authors show that corporate image associations with innovation and trustworthiness (but not social responsibility) influence product evaluations more when consumers perceive high (versus low) risk in the product purchase. Their findings extend previous research by identifying perceived risk as a moderator of the effects of corporate image on product evaluations. The authors discuss implications for the conditions governing the “flow-through” of corporate image to individual product eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
192
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(214 citation statements)
references
References 25 publications
12
192
1
2
Order By: Relevance
“…Co-branding partners may have dissimilar organizational characteristics (De Man, 2013) that can hardly be manipulated. They often unintentionally affect customers' brand fit perceptions and attitudes (Connelly et al, 2011;Gürhan-Canli and Batra, 2004). Because the similarity of co-branding partners leads to the perception of a higher brand fit (Simonin and Ruth, 1998), we argue that firms with dissimilar organizational characteristics in terms of size, age, industry scope, and country-of-origin image, which cannot be aligned on short notice, provide potentially unintended market signals and, in turn, achieve lower brand fit evaluations.…”
Section: Signaling Theorymentioning
confidence: 92%
“…Co-branding partners may have dissimilar organizational characteristics (De Man, 2013) that can hardly be manipulated. They often unintentionally affect customers' brand fit perceptions and attitudes (Connelly et al, 2011;Gürhan-Canli and Batra, 2004). Because the similarity of co-branding partners leads to the perception of a higher brand fit (Simonin and Ruth, 1998), we argue that firms with dissimilar organizational characteristics in terms of size, age, industry scope, and country-of-origin image, which cannot be aligned on short notice, provide potentially unintended market signals and, in turn, achieve lower brand fit evaluations.…”
Section: Signaling Theorymentioning
confidence: 92%
“…Hence, the moderating role of risk perception related to online shopping is an important topic that has not received enough consideration in the literature. Some researchers have studied the moderating effect of risk perception on the link between trust and shopping behavior or intention (Büttner and Göritz, 2008), on the effect of brand image or reputation on the evaluation of a supplier or a product (Gurhan-Canli and Batra, 2004), on the impact of satisfaction on online trust (San Martin and Camarero, 2009), on the predictor of trust (Martin and Camarero, 2009), or on some links of the Technology Acceptance Model (TAM) (Featherman and Fuller, 2002). San Martin and Camarero (2009) reported that "Since the results partly corroborate the theoretical assumptions, it is necessary to keep working in this line and increase the number of papers using perceived risk as a moderating variable.…”
Section: Jssmentioning
confidence: 99%
“…The customer may reason that doing business with a low-CA company will increase the probability of losing money (cf. Gürhan-Canli and Batra, 2004). Similarly, an investor may reason that a companyÕs CA will likely impact the companyÕs financial performance, and therefore the returns he or she will get from a companyÕs stocks.…”
Section: The Personal Relevance Of Ca Informationmentioning
confidence: 99%